ENGARUH PELATIHAN PENANGANAN PERTAMA CEDERA KEPALA TERHADAP PENGETAHUAN SISWA SMAN 6 MALANG - Christianingsih, Siska; Wihastuti, Titin Andri; Fathoni, Mukhamad (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2017)
Head injuries still a health problem that has serious consequences for the sufferer, wheretrauma is the leading cause of death. The most common cause is a motor vehicle accident. Thehighest prevalence of injury is in the age group 15-24 years (11.7%). The lack of communitycompetence in preventing secondary injury that often accompanies the patient and is the maincause of death. This study aim to analyze the effect of head injuries first aid to increaseknowledge in students of SMA Negeri 6 Malang. The method in this research was quasyexperimental. The samples was 52 respondents using proportionate stratified random samplingtechnique. The result of independent t test showed that there was significant difference inknowledge variable (0,017). The need for training in common people to recognize the needs andprovide appropriate early care to victims of acute trauma and can provide more accurateinformation to the ambulance.